2021
DOI: 10.4187/respcare.09283
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Burnout Among Respiratory Therapists Amid the COVID-19 Pandemic

Abstract: BACKGROUND: Burnout is a major challenge in health care, but its prevalence has not been evaluated in practicing respiratory therapists (RTs). The purpose of this study was to identify RT burnout prevalence and factors associated with RT burnout. METHODS: An online survey was administered at 26 centers in the United States between January and March 2021. Validated quantitative cross-sectional surveys were used to measure burnout and leadership domains. The survey was sent to department directors and distribute… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(25 citation statements)
references
References 35 publications
0
25
0
Order By: Relevance
“…Respiratory therapists (RTs) are among the healthcare professionals exposed to burnout at the workplace. Recently, 79% of respiratory therapists reported burnout in a survey among 1114 respiratory therapists from 26 medical centers in the United States [ 6 ], mainly due to high patient morbidity and mortality as well as heavy workloads in the critical care units [ 6 ]. A recent cross-sectional study conducted in a tertiary hospital in Saudi Arabia also reported high levels of the three domains of burnout among RTs: 77% with emotional exhaustion, 98% with depersonalization, and 73% with low personal achievement [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Respiratory therapists (RTs) are among the healthcare professionals exposed to burnout at the workplace. Recently, 79% of respiratory therapists reported burnout in a survey among 1114 respiratory therapists from 26 medical centers in the United States [ 6 ], mainly due to high patient morbidity and mortality as well as heavy workloads in the critical care units [ 6 ]. A recent cross-sectional study conducted in a tertiary hospital in Saudi Arabia also reported high levels of the three domains of burnout among RTs: 77% with emotional exhaustion, 98% with depersonalization, and 73% with low personal achievement [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…20 Burnout among healthcare professionals amid the COVID-19 pandemic in Saudi Arabia is consistent with those reported by other countries around the world. 8,21 This consistency among different geographical areas shows that despite the differences in the economic resources of each country, religious beliefs, or cultural differences, burnout is a rising global health concern due to the COVID-19 pandemic. Burnout affects the quality of care delivered to patients by increasing the incidence of medical errors.…”
Section: Correlation Between Burnout and Years Of Experiencementioning
confidence: 99%
“…Due to this work environment, RTs are exposed to high levels of stress while providing optimal care and communicating with patients. 8 However, burnout and job dissatisfaction can negatively impact the productivity of RTs. A recent study conducted in the United States to investigate burnout among RTs showed that 79% of RTs reported burnout, with more than 40% experiencing moderate and severe burnout.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“… 8 While the focus of this paper is on physicians, the frequency of burnout and impact are similarly felt among other health care professionals. 9 , 10 …”
Section: Introductionmentioning
confidence: 99%